Neonatal pain and reduced maternal care alter adult behavior and hypothalamic–pituitary–adrenal axis reactivity in a sex‐specific manner. Issue 5 (1st December 2019) - Mooney‐Leber, Sean M.; Brummelte, Susanne
Abstract: Preterm infants often spend a significant amount of time in the neonatal intensive care unit (NICU) where they are exposed to many stressors including pain and reduced maternal care. These early‐life stressful experiences can have negative consequences on brain maturation during the neonatal period; however, less is known about the long‐term cognitive and affective outcomes. Thus, this study was conducted to investigate the impact of neonatal pain and reduced maternal care on adult behavior and HPA axis reactivity in an animal model. Male and female rats underwent a series of repetitive needle pokes and/or reduced maternal care (through a novel tea ball infuser encapsulation method) during the first 4 days of life and were then assessed in a battery of behavioral tests as adults. We found that early‐life pain enhanced spatial learning independent of the animal's sex, but altered HPA recovery from an acute stressor in females only. Moreover, reduced maternal care altered long‐term spatial memory and reversal learning in males. These findings indicate that neonatal stressors have unique sex‐dependent long‐term biobehavioral effects in rodents. Continued examination of the behavioral consequences of these stressors may help explain varying vulnerability and resiliency in preterm infants who experienced early stress in the NICU.